Importance of Protein-tyrosine Phosphatase-α Catalytic Domains for Interactions with SHP-2 and Interleukin-1-induced Matrix Metalloproteinase-3 Expression - Wang, Qin (American Society for Biochemistry and Molecular Biology, 2010)
Interleukin-1 (IL-1) induces extracellular matrix degradation as a result of increased expression of matrix metalloproteinases (MMPs). We examined adhesion-restricted signaling pathways that enable IL-1-induced MMP release in human gingival and murine fibroblasts. Of the seven MMPs and three tissue inhibitors of MMPs screened, IL-1 enhanced release only of MMP3 when cells formed focal adhesions. Inhibition of protein-tyrosine phosphatases (PTPs), which are enriched in focal adhesions, blocked IL-1-induced MMP3 release. Accordingly, in contrast to wild-type cells, fibroblasts null for PTPα did not exhibit IL-1-induced MMP3 release. IL-1 treatment enhanced the recruitment of SHP-2 and PTPα to focal adhesions and the association of PTPα with SHP-2. Pulldown assays confirmed a direct interaction between PTPα and SHP-2, which was dependent on the intact, membrane-proximal phosphatase domain of PTPα. Interactions between SHP-2 and PTPα, recruitment of SHP-2 to focal adhesions, IL-1-induced ERK activation, and MMP3 expression were all blocked by point mutations in the phosphatase domains of PTPα. These data indicate that IL-1-induced signaling through focal adhesions leading to MMP3 release and interactions between SHP-2 and PTPα are dependent on the integrity of the catalytic domains of PTPα.